2023
DOI: 10.3390/nano13061015
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Adsorption and Characteristics of Iron, Cobalt, and Nickel Oxides Impregnated on SBA-15 Mesoporous Silica

Abstract: Hexagonal SBA-15 mesoporous material was used as a catalytic template for impregnation, with the transition metals Fe, Co, and Ni as catalysts for chemical transformation. Nitrogen adsorption/desorption isotherms, scanning electron microscopy, and transmission electron microscopy were conducted to better understand the physicochemical properties of the metal oxide-impregnated SBA-15. The specific surface area of the original SBA-15 was approximately 680 m2/g, and the abundances of the catalysts impregnated ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Nitrogen adsorption and desorption measurements were used to characterize the porous structure of CNS AC. The hysteresis loop in the relative pressure range of 0.3-1.0 (Figure 2) is a sign of Type IV isotherm according to the IUPAC classification, indicating the presence of mesopores in the CNS AC structure [24,25]. This is further supported by the BJH pore size distribution (inset in Figure 2), which shows that the pore diameters are less than 4 nm, with micropores (< 2 nm) being the dominant pore type.…”
Section: Analysis Of Porous Structurementioning
confidence: 64%
“…Nitrogen adsorption and desorption measurements were used to characterize the porous structure of CNS AC. The hysteresis loop in the relative pressure range of 0.3-1.0 (Figure 2) is a sign of Type IV isotherm according to the IUPAC classification, indicating the presence of mesopores in the CNS AC structure [24,25]. This is further supported by the BJH pore size distribution (inset in Figure 2), which shows that the pore diameters are less than 4 nm, with micropores (< 2 nm) being the dominant pore type.…”
Section: Analysis Of Porous Structurementioning
confidence: 64%
“…SBA-15 featuring a large surface area, abundant mesoporous channels, and remarkable hydrothermal stability has drawn tremendous attention as an efficient catalytic material or supporting matrices for active components. In addition, the fascination of SBA-15 also comes from the easy modification because of the existence of plentiful surface Si–OH groups. , Especially, the platelet-like ZrSBA-15 with short mesoporous channels as the support benefit to improve the catalytic performance compared with traditional SBA-15 . For example, Zhai et al reported that the phosphotungstic acid catalyst supported by a platelet-like ZrSBA-15 demonstrated highly improved catalytic activity for the selective oxidation of benzyl alcohol .…”
Section: Introductionmentioning
confidence: 99%